Strategies for Talent’s Digital Competence Development at Higher Vocational Colleges for Digital Transformation - Zeng, Xiuzhen; Li, Yaxin (Journal of Education, Health and Sport, 2022)
Digital transformation has brought unprecedented opportunities and challenges to economic and social development, and the development of talent’s digital competence is of growing importance. Under an ideal situation, digitization, digitalization and digital transformation are three stages of gradual digital development. However, influenced by the difference in social and economic development among regions, higher vocational colleges, as an educational system closest to the labor market, vary by their own strengths and digital competence. From the perspective of game theory and based on the model of the boxed pig game, this paper provides strategies and suggestions for the cultivation of talent’s digital competence in terms of non-cooperative strategy at higher vocational colleges. The supply-demand model of talent’s digital competence cultivation is established to provide further suggestions for the top-down cooperation strategy among higher vocational colleges.